Prawa i obowiązki rodziców w kontekście zadań szkoły - Stawniak, Henryk (Prawo Kanoniczne, 2007)
The article analyzes educational rights and obligations of parents which are realized through schools, including denominational schools and especially Catholic schools. It shows school’s tasks and possibility of joining parents into the triad of teaching, educating and evangelizing. The essay stresses these elements of school structure in which parents can participate and influence the way that schools are running. It answers the question about the mutual relationship between school administration and parents. Should we go in the direction of vivid dialog between parents and school or go further-parents should co-run schools.